The Efficacy and Safety of Topiramate for Prophylaxis of Migraine in Children - FALLAH, Razieh; AKHAVAN KARBASI, Sedighah; SHAJARI, Ahmad; FROMANDI, Mostafa (Iranian Journal of Child Neurology, 2013)
How to Cite This Article: Fallah R, Akhavan Karbasi S, Shajari A, Fromandi M. The Efficacy and Safety of Topiramate for Prophylaxis of Migraine in Children. Iran J Child Neurol. 2013 Autumn; 7(4):7-11. Objective Migraine is the most common acute intermittent primary headache in children and prophylactic therapy is indicated in children with frequent or disabling headaches. The purpose of this study was to evaluate the efficacy and safety of topiramate (TPM) for migraine prophylaxis in children. Materials & Methods In a quasi-experimental study, monthly frequency, severity and duration of headache, migraine disability, and side-effects were evaluated in 100 children who were referred to the Pediatric Neurology Clinic of Shahid Sadoughi University of Medical Sciences, Yazd, Iran from April 2011 to March 2012, and were treated with 3 mg/kg/day of TPM for three months. Results Fifty eight (57.4%) girls and 42 (41.6%) boys with the mean age of 10.46±2.11 years were evaluated. Monthly frequency, severity, and duration of headache decreased with treatment from 15.34±7.28 to 6.07±3.16 attacks, from 6.21±1.74 to 3.15±2.22, and from 2.28±1.55 to 0.94±0.35 hours, respectively, and the Pediatric Migraine Disability Assessment score reduced with TPM from 32.48±9.33 to 15.54±6.16. Transient side-effects were seen in 21% of the patients, including hyperthermia in 11%, anorexia and weight loss in 6%, and drowsiness in 4%. No serious side-effects were reported. Conclusion TPM could be considered as a safe and effective drug in pediatric migraine prophylaxis. References Hershey AD. Migraine. In: Kliegman RM, Stanton BF, Schor NF, St. Geme JW, Behrman RE, editors Nelson Textbook of Pediatrics. 19th ed. Philadelphia: Saunders; 2011. p. 2040-5. The International Classification of Headache Disorders:2nd ed. Headache Classification Subcommittee of the International Headache Society. Cephalalgia 2004;24 Suppl 1:9-160. Hershey AD, Winner PK. Pediatric migraine: recognition and treatment. J Am Osteopath Assoc 2005;105(4 Suppl 2):2S-8S. Jayapal S, Maheshwari N. Question 3. Topiramate for chronic migraine in children. Arch Dis Child 2011;96(3):318-21. Fallah R. Topiramate as a new antiepileptic drug in epileptic children in Iran. Indian J Pediatr 2006;73(12):1073-5. Hershey AD, Powers SW, Vockell ALB, LeCates SL, Kabbouche MA, Maynard MK. PedMIDAS: Development of a questionnaire to assess disability of migraines in children. Neurology 2001;57(11):2034-9. Wewers ME, Lowe NK. A critical review of visual analogue scales in the measurement of clinical phenomena. Res Nurs Health 1990;13(4):227-36. Ashtari F, Shaygannejad V, Akbari M. A doubleblind, randomized trial of low-dose topiramate vs propranolol in migraine prophylaxis. Acta Neurol Scand 2008;118(5):301-5. Tonekaboni SH, Ghazavi A, Fayyazi A, Khajeh A, Taghdiri MM, Abdollah Gorji F, Azargashb E.Prophylaxis of childhood migraine: Topiramate versus Propranolol. Iran J Child Neurol 2013 ; 7(1):9-14. Winner P, Pearlman EM, Linder SL, Jordan DM, Fisher AC, Hulihan J; Topiramate Pediatric Migraine Study Investigators. Topiramate for migraine prevention in children: a randomized, double-blind, placebo-controlled trial. Headache 2005;45(10):1304-12. Lewis D, Winner P, Saper J, Ness S, Polverejan E, Wang S, et al. Randomized, double-blind, placebo-controlled study to evaluate the efficacy and safety of topiramate for migraine prevention in pediatric subjects 12 to 17 years of age. Pediatrics 2009;123(3):924-34. Borzy JC, Koch TK, Schimschock JR. Effectiveness of topiramate in the treatment of pediatric chronic daily headache. Pediatr Neurol 2005;33(5):314-6. Campistol J, Campos J, Casas C, Herranz JL. Topiramate in the prophylactic treatment of migraine in children. J Child Neurol 2005;20(3):251-3. Cruz MJ, Valencia I, Legido A, Kothare SV, Khurana DS, Yum S, et al. Efficacy and tolerability of topiramate in pediatric migraine. Pediatr Neurol 2009;41(3):167-70. Aydin M, Kabakus N, Bozdag S, Ertugrul S. Profile of children with migraine. Indian J Pediatr 2010;77(11):1247-51. Unalp A, Uran N, Oztürk A. Comparison of the effectiveness of topiramate and sodium valproate in pediatric migraine. J Child Neurol 2008;23(12):1377-81. Lakshmi CV, Singhi P, Malhi P, Ray M. Topiramate in the prophylaxis of pediatric migraine: a double-blind placebo-controlled trial. J Child Neurol 2007;22(7):829-35. Vollono C, Ferraro D, Valeriani M. Antiepileptic drugs in the preventive treatment of migraine in children and adolescents. Drug Development Research 2007;68:355-9. 19. Ferraro D, Di Trapani G. Topiramate in the prevention of pediatric migraine: literature review. J Headache Pain 2008;9(3):147-50.